Accuracy of Visual Fields in Localizing MRI Lesions in Posterior Cerebral Artery Infarction. Issue 3 (14th September 2022) - Cho, Juno; Liao, Eric; Trobe, Jonathan D.
Abstract : Background: The representation of the visual field in visual cortex was established over a century ago by correlating perimetric defects with the estimated location of war wounds. The availability of high-definition MRI offers the possibility of more precise correlation. Methods: Homonymous hemianopias disclosed on automated visual fields (HVFs) were drawn from an electronic medical record search from 2009 to 2020 at the Michigan Medicine, a tertiary care academic medical center. The patterns of the visual field defects (VFDs) were interpreted by a consensus of 2 authors. The VFDs were correlated with the location of MRI lesions in 92 patients with posterior cerebral artery (PCA) domain ischemic strokes, as determined by the neuroradiologist author, who was masked as to the VFDs. Results: Among the 77 VFDs confined to 1 hemifield, 74 (96%) correctly predicted the side of the visual cortex lesion. In 3 cases, the MRI lesion in the opposite cerebral hemisphere was not foretold. Among the 15 VFDs present in both hemifields, 5 (33.3%) overestimated the MRI lesions, which were evident in only 1 hemisphere. Among the 30 VFDs confined to 1 quadrant, 29 (97%) correctly predicted the lesioned visual cortex quadrant. However, 14 VFDs failed to predict MRI lesions present in both superior and inferior visual cortex quadrants on the same side. Those unpredicted lesions mostly had subtle or indistinct signal abnormalities or were confined to anterior visual cortex, an area that is inaccessible with the HVF test protocol used in this study. Conclusion: In this study of PCA ischemic stroke, VFDs limited to 1 hemifield were accurate in locating the side and quadrant of the MRI visual cortex lesions. However, the quadrantic VFDs sometimes failed to predict that the lesions involved both the superior and inferior quadrants on the same side, largely because those lesions had subtle imaging features that defied accurate radiologic assessment or were out of the reach of the visual field test protocol.